O Garimpo Bom Futuro como ferramenta para o ensino de química e da educação ambiental - Zan, Renato André (2012)
Bom Futuro mining is called the largest open pit gold mining in the world, was discovered in 1987and from this discovery began with the digging of its greatest wealth is cassiterite (SnO2), whichcontains about 66% to 75% tin, and is passed through a beneficiation process, which leaves herwith a tin of 99.98% purity. This ore is used in various purposes such as, tin and alloys as solder,brass, pewter alloy and chemical compounds. The tin helped and continues to help the economyof the state of Rondonia, being increasingly used in our day to day, knowing the potential size ofthe study, this paper aims to propose a visit from mining as a tool in teaching environmentaleducation and chemistry, giving a different look to a gold mining and show the great potential of mining as a major laboratory in the open.